Ventrolateral medulla mechanisms involved in cardiorespiratory responses to central chemoreceptor activation in rats - Takakura, Ana C. [UNESP]; Colombari, Eduardo [UNESP]; Menani, José Vanderlei [UNESP]; Moreira, Thiago S. (Amer Physiological Soc, 2011)
A rise in arterial PCO2 stimulates breathing and sympathetic activity to the heart and blood vessels. In the present study, we investigated the involvement of the retrotrapezoid nucleus (RTN) and glutamatergic mechanisms in the Botzinger/C1 region (Botz/C1) in these responses. Splanchnic sympathetic nerve discharge (sSND) and phrenic nerve discharge (PND) were recorded in urethane-anesthetized, sino-aortic-denervated, vagotomized, and artificially ventilated rats subjected to hypercapnia (end-expiratory CO2 from 5% to 10%). Phrenic activity was absent at end-expiratory CO2 of 4%, and strongly increased when end-expiratory CO2 reached 10%. Hypercapnia also increased sSND by 103 +/- 7%. Bilateral injections of the GABA-A agonist muscimol (2 mM) into the RTN eliminated the PND and blunted the sSND activation (Delta = +56 +8%) elicited by hypercapnia. Injections of NMDA receptor antagonist AP-5 (100 mM), non-NMDA receptor antagonist 6,7-dinitro-quinoxaline-2,3-dione (DNQX; 100 mM) or metabotropic glutamate receptor antagonist (+/-)-alpha-methyl-4-carboxyphenylglycine (MCPG; 100 mM) bilaterally into the Botz/C1 reduced PND (Delta = +43 +/- 7%, +52 +/- 6% or +56 +/- 11%, respectively). MCPG also reduced sSND (Delta = +41 +/- 7%), whereas AP-5 and DNQX had no effect. In conclusion, the increase in sSND caused by hypercapnia depends on increased activity of the RTN and on metabotropic receptors in the Botz/C1, whereas PND depends on increased RTN activity and both ionotropic and metabotropic receptors in the Botz/C1.
Keywords: chemoreflex; sympathetic activity; phrenic nerve